Impact of Predilation During Transcatheter Aortic Valve Replacement: Insights From the PARTNER 3 Trial. (18th June 2021) - Ternacle, Julien; Al-Azizi, Karim; Szerlip, Molly; Potluri, Srinivasa; Hamandi, Mohanad; Blanke, Philipp; Leipsic, Jonathon; Dahou, Abdellaziz; Salaun, Erwan; Vincent, Flavien; Rogers, Erin; Alu, Maria C.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The use of predilation during transcatheter aortic valve replacement (TAVR) is variable, and its association with outcomes remains unknown. We evaluated the impact of predilation versus no predilation (direct TAVR) in the low-risk population enrolled in the PARTNER 3 trial (Placement of Aortic Transcatheter Valves). Methods: In the PARTNER 3 trial, 495 patients with severe symptomatic aortic stenosis underwent TAVR with the SAPIEN 3 valve. The use of predilation was left to operator discretion. The primary end point was a composite of all-cause death, stroke, or rehospitalization. Secondary end points included valve hemodynamic performance and the need for postdilation. Propensity score matching was performed. Results: Predilation and direct TAVR were performed in 286 (57.8%) and 209 (42.2%) patients, respectively. Before matching, the primary end point occurrence at 30 days (3.8% versus 4.8%, P =0.604) and 1 year (8.7% versus 8.1%, P =0.831) was similar in the predilation versus direct TAVR groups. Similar results were observed after matching (202 patients in each groups). Incidence of ≥ mild paravalvular regurgitation was similar in both groups. Incidence of severe prosthesis-patient mismatch was low but higher in the predilation group versus the direct TAVR group (8.2% versus 2.6%, P =0.023). Compared with direct TAVR, the use of predilation was associated with longer procedure duration (63.2 versus 51.4 minutes, P =0.001), while the rate of postdilation did not differ between the 2 groups (24.8% versus 18.8%, P =0.150). Conclusions: Predilation and direct TAVR are safe in patients with low surgical risk and favorable aortic valve anatomy. Direct TAVR decreased the procedure duration and did not predispose to more postdilation. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02675114.